The comparative value of hand-watering vs. self-watering fattening pigs on sudangrass pasture. - Aubel, C.E. (Kansas Agricultural Experiment Station, 2011)
This experiment to compare two methods of watering pigs was conducted in the summer of 1956 with spring pigs on pasture. Two lots of 10 pigs each were fed shelled corn and, a mixed animal and plant protein supplement of 4 parts tankage, 4 parts soybean meal, 1 part linseed meal, and 1 part alfalfa meal. Both lots were self-fed, free-choice, on sudangrass pasture.
Keywords: Swine; hand-watering vs. self-watering; Sudangrass